2022
DOI: 10.1038/s41420-022-01113-2
|View full text |Cite
|
Sign up to set email alerts
|

The role of N6-methyladenosine-modified non-coding RNAs in the pathological process of human cancer

Abstract: Non-coding RNAs (ncRNAs) account for the majority of the widespread transcripts of mammalian genomes. They rarely encode proteins and peptides, but their regulatory role is crucial in numerous physiological and pathological processes. The m6A (N6-methyladenosine) modification is one of the most common internal RNA modifications in eukaryotes and is associated with all aspects of RNA metabolism. Accumulating researches have indicated a close association between m6A modification and ncRNAs, and suggested m6A-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 140 publications
(147 reference statements)
0
6
0
Order By: Relevance
“…Conversely, Shen et al ( 123 ) found that the degradation of long ncRNA (lncRNA) FENDRR mediated by YTHDF2 stimulated cell proliferation in EC. NcRNAs are associated with m6A modification, thereby affecting gene expression and the development of cancer ( 124 ). LncRNA FENDRR is a well-known tumor suppressor gene in several malignancies, including breast cancer ( 125 ), colon cancer ( 126 ) and prostate cancer ( 127 ).…”
Section: M6a and Ecmentioning
confidence: 99%
“…Conversely, Shen et al ( 123 ) found that the degradation of long ncRNA (lncRNA) FENDRR mediated by YTHDF2 stimulated cell proliferation in EC. NcRNAs are associated with m6A modification, thereby affecting gene expression and the development of cancer ( 124 ). LncRNA FENDRR is a well-known tumor suppressor gene in several malignancies, including breast cancer ( 125 ), colon cancer ( 126 ) and prostate cancer ( 127 ).…”
Section: M6a and Ecmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) modification is firstly described in 1971 years, which has shown critical roles in mRNA metabolism and become focus recently ( Chen et al, 2022 ; Li et al, 2022 ). Methyltransferase installed the m 6 A modification on mRNA, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and the Wilms tumor 1-associated protein (WTAP) ( Lin et al, 2022 ; Luo et al, 2022 ). In addition, the m 6 A modification was wiped by demethylase, including obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5) ( Qin et al, 2022 ; Zhai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we included information specifically on the N 6 -methyladenosine (m 6 A) modification, offering a more detailed understanding of its influence. Luo et al concluded a critical facet of lncRNA biology is the m 6 A modification; it represents the most predominant internal modification observed in eukaryotic RNAs, including lncRNAs, exerting a pivotal role in RNA metabolism and functionality [7]. The modulation of lncRNA structures and functions by m 6 A introduces additional layers of regulatory intricacy [7,8].…”
Section: Introductionmentioning
confidence: 99%